PENGARUH PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS XI SMAN 6 PARIAMAN - Hanifa, Wahyu Putri (Jurnal Edukasi dan Penelitian Matematika, 2024)
One of the most important aspects of mastering mathematics is developing problem-solving skills. It would appear from initial observations that students are struggling to solve tasks requiring them to use signals. The purpose of this study is to analyse how SMAN 6 Pariaman's instructional use of the CPS paradigm affected student achievement. Four indicators are used to evaluate this model. These four measures are used to test the mathematical problem-solving ability of students in class XI of SMAN 6 Pariaman. Exam results show that students struggle to become proficient problem solvers, which leads us to this conclusion. The study used a quasi-experimental design with a control group that only participated in the post-test. Participants were pupils enrolled in the 2024–2025 school year from class XI at SMAN 6 Pariaman. Classes XI F 3 and XI F 1 served as the experimental and control groups, respectively. A test with essay questions is used for evaluation. A t-test data analysis produced a 0.002 P-value. As a result, we can say that H0 is not true. As a result, as compared to more conventional approaches to learning mathematics, the CPS model used in SMAN 6 Pariaman, class XI, yields better results.Keywords– Mathematical problem solving abilities, creative problem solving models and                    quasi experiment